Bank Diversification, Performance and Cash Holdings: Evidence from Pakistan - Kamran, Muhammad Rizwan; Shoaib, Touqir; Mumtaz, Raheel; Choudhary, Adnan Ali (Pakistan Journal of Humanities and Social Sciences, 2022)
The current study explores the moderating impact of cash holdings on the relationship between bank diversification and bank performance. For doing this, the data for the period of 2009 to 2019 for 18 banking firms are gathered from annual reports and the business recorder websites. Return on assets, profit ratio, Tobin q, and cost to income ratio are utilized as dependent, income diversity is taken as independent, cash positions, and cash conversion cycle, and liquidity are used as moderating while bank size, capital ratio, loan loss provision ratio, and loan ratio are used as control variables. Regression analysis is applied to analyze the impact of cash holdings on the bank diversification and performance link. The findings of the study show that income diversification, cash positions, cash conversion cycle, and liquidity have a positive impact on the bank's performance (measured by return on assets, profit ratio, and cost-to-income ratio). Income diversification has a non-significant impact on Tobin Q while cash positions, cash conversion cycle, and liquidity have a significant positive impact on Tobin Q. Moreover, all measures of cash holdings (cash positions, cash conversion cycle, and liquidity) moderate the relation between bank diversification and performance as the coefficients of income diversity become more significant with the inclusion of moderating force. The findings suggest increasing income diversity in banks in order to improve bank performance. The study also recommends considering cash holdings as a strengthening force in the relationship between bank diversification and performance.